Electrically Conducting Hydrogel Graphene Nanocomposite Biofibers for Biomedical Applications - Talebian, Sepehr; Mehrali, Mehdi; Raad, Raad; Safaei, Farzad; Xi, Jiangtao; Liu, Zhoufeng; Foroughi, Javad (Frontiers in Chemistry, 2020)
Conductive biomaterials have recently gained much attention specifically due to their application for electrical stimulation of electrically excitable cells. Herein, flexible, electrically conducting, robust fibres comprised of both an alginate biopolymer and graphene components have been produced using a wet-spinning process. These nanocomposite fibers showed better mechanical, electrical and electrochemical properties when compared to single fibers that were made solely from alginate. Furthermore, with the aim of evaluating the response of biological entities to these novel nanocomposite biofibers, in vitro studies were carried out using C2C12 myoblast cell lines. The obtained results from in vitro studies indicated that the developed electrically conducting biofibers are biocompatible to living cells and encouraged their proliferation and differentiation. The developed hybrid conductive biofibers are likely to find applications as 3D scaffolding materials for tissue engineering applications.